A responsabilização civil do fornecedor de crédito pelos empréstimos consignados não autorizados aos consumidores idosos - Balbinot, Erica (2024)
This article seeks to analyze the nature of the credit provider's civil liability, in light of the Consumer Protection Code (CDC), for unauthorized loans granted to elderly consumers. The problem is justified considering that the large supply of credit available to consumers and new technologies encourage fraud against consumers in payroll loan contracts. Therefore, the nature of the civil liability of finance companies is investigated when a loan is contracted by a third party, without the consumer's consent. To this end, the objective is to understand the granting of credit and the vulnerability of elderly consumers, to study payroll loans, as well as to discuss the civil liability of credit providers. Based on the hermeneutic method, it appears that banking/financial institutions are considered suppliers, as they act as service providers to consumers, and are therefore subject to CDC standards. In the case of unauthorized payroll loans, they have objective civil liability and must compensate consumers for material and moral damages. The damage is presumed and arises from the breach of safety and protection duties on the part of suppliers, which, in turn, receive a greater dimension when the consumer is elderly, therefore hypervulnerable.